Efeito do cloreto de sódio na dieta, dureza e ph da água na sobrevivência, crescimento e fluxos iônicos de juvenis de jundiá (Rhamdia quelen) - Copatti, Carlos Eduardo (2008)
The purpose of this study was to verify the effect of dietary salt (NaCl) supplementation, water hardness and pH on growth, survival and ionoregulation of silver catfish (Rhamdia quelen) juveniles. In the first experiment, juveniles were fed with diets supplemented with 0.0; 0.5; 1.0 e 2.0 % NaCl and exposed to pH 5.5, 7.0 and 9.0 for 35 days. In the second study, fish were maintained for 30 days in three different pH (5.5; 7.0 and 9.0) and four water hardness (30, 60, 120, and 180 mg L-1 CaCO3). The third experiment investigated the effects of the 6.0-8.0 pH range at low water hardness (0, 25 and 50 mg L-1 CaCO3) for 32 days. In the experiments 1 and 2, fish samples were collected at different moments for analyses of Na+, K+ and Cl- net ion fluxes. In all three studies, growth and survival were analyzed. The water utilized was previously adjusted to the appropriate pH and water hardness using NaOH or H2SO4 0.5 M and CaCl2.2H2O, respectively. In the first experiment, fish fed with diet without NaCl supplementation and exposed to pH 7.0 presented significantly higher weight, length, SGR and biomass per tank than those exposed to pH 5.5, and the increase of dietary NaCl protected against the impact of acidic water. Dietary salt supplementation contributed to decrease the osmoregulatory disturbances in the juveniles exposed to acidic or basic pH. In the second study, exposure of juveniles to alkaline or acidic water did not affect survival, but acidic water reduced growth. And, finally, in the third study, juveniles exposed to pH 7.0 and 8.0 at zero water hardness showed significantly higher mortality than those kept at pH 6.0. Survival and growth of juveniles exposed to 25 and 50 mg L-1 CaCO3 was not affected in the 6.0-8.0 pH range. Therefore, the best water hardness for silver catfish juveniles growth and osmoregulation is 30-60 mg L-1 CaCO3 and at low water hardness (next zero) pH must be reduced. It can be concluded that the interaction of dietary salt, pH and water hardness are very important to silver catfish rearing, because they change growth and ionoregulation in this species.